1982
DOI: 10.1111/j.1751-1097.1982.tb04393.x
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation and Singlet Oxygen Sensitization by Protoporphyrin Ix and Its Photooxidation Products

Abstract: Protoporphyrin IX and its various ester derivatives have been previously shown to undergo self‐sensitized photooxygenation to yield hydroxyaldehydes (photoprotoporphyrin) and mono‐ and diformyl deuteroporphyrin derivatives. In the present study the photoreactions of these products in the presence of oxygen have been investigated. All of the photooxidation products are themselves good sensitizers of singlet oxygen. In addition spin trapping experiments indicate these products can produce superoxide in low‐to‐mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 18 publications
2
42
1
Order By: Relevance
“…Recently, there are reports on the important role of singlet oxygen on photosensitization by miscellaneous dyes (1,2,4,7,14) and a function of NaN3 as an antioxidant in photooxidation (5,9,14). On the basis of the data, NaN3 of a disinfectant in this experiment might have acted as a singlet oxygen scavenger in the virus-dye mixtures, in contrast with so-called sensitized photochemical reactions involving oxygen.…”
Section: Discussionmentioning
confidence: 73%
“…Recently, there are reports on the important role of singlet oxygen on photosensitization by miscellaneous dyes (1,2,4,7,14) and a function of NaN3 as an antioxidant in photooxidation (5,9,14). On the basis of the data, NaN3 of a disinfectant in this experiment might have acted as a singlet oxygen scavenger in the virus-dye mixtures, in contrast with so-called sensitized photochemical reactions involving oxygen.…”
Section: Discussionmentioning
confidence: 73%
“…Preliminary analysis by HPLC also indicated that a small amount (, 10%) of Ppp was formed when exposing the cells to light (data not shown). In view of this and the data from other groups (Inhoffen et al, 1969;Krieg and Whitten, 1984, a and b;Cox et al, 1982), we assume that Ppp is formed as the major fluorescing photoproduct with fluorescence spectra different from those of Pp IX. Ppp seems to be formed by the action of 1 O 2 , as indicated by the increased yield in D 2 O buffer ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given in excess, exogenous ALA thus can result in a temporary accumulation of PpIX, in particular, in cells with higher metabolic turnover. Since PPIX has fairly good photosensitizing properties (Cox et al, 1982;Kennedy et al, 1990) proposed ALA as a possible photodynamic agent. Following this pioneering work, this treatment modality has been widely studied for various cancers (Kennedy et al, 1992;Peng et al, 1992;Svanberg et al, 1994).…”
mentioning
confidence: 99%